Cisplatin-induced hyponatremia in malignancy: comparison between brand-name and generic formulation - Ochi N; Yamane H; Hotta K; Fujii H; Isozaki H; Honda Y; Yamagishi T; Kubo T; Tanimoto M; Kiura K; Takigawa N (Dove Medical Press, 2014)
Nobuaki Ochi,1,2 Hiromichi Yamane,1 Katsuyuki Hotta,3 Hiromi Fujii,4 Hideko Isozaki,2,5 Yoshihiro Honda,1,2 Tomoko Yamagishi,1 Toshio Kubo,6 Mitsune Tanimoto,2,3 Katsuyuki Kiura,6 Nagio Takigawa1 1Department of General Internal Medicine 4, Kawasaki Hospital, Kawasaki Medical School, Okayama, Japan; 2Department of Hematology, Oncology and Respiratory Medicine, Okayama University Graduate School of Medicine, Dentistry, and Pharmaceutical Sciences, Okayama, Japan; 3Department of Hematology and Oncology, Okayama University Hospital, Okayama, Japan; 4Department of Pharmacy, Kawasaki Hospital, Kawasaki Medical School, Okayama, Japan; 5Department of Clinical Pharmaceutics, Okayama University Graduate School of Medicine, Dentistry, and Pharmaceutical Sciences, Okayama, Japan; 6Department of Respiratory Medicine, Okayama University Hospital, Okayama, Japan Introduction: Widespread use of generic drugs is considered to be indispensable if reductions in total health care costs are to be achieved, but the market share of such drugs remains low. In general, generic drugs have the same active ingredients as brand-name drugs, but this is not always the case. Thus, toxicity profiles may vary when brand-name and generic drugs are compared. We retrospectively investigated the incidence of hyponatremia in patients receiving brand-name cisplatin (CDDP) and a generic counterpart thereof. Methods: We reviewed the medical records of patients treated with brand-name CDDP (n=53) and a generic formulation (n=26), and compared the incidences of hyponatremia and renal toxicity. Toxicities were graded using the Common Terminology Criteria for Adverse Events, version 4.0. Differences between groups were evaluated using the Student’s t-test, and the odds ratio for hyponatremia was estimated via logistic regression analysis. Results: Serum creatinine levels after chemotherapy increased significantly in both the brand-name and generic CDDP groups; no significant difference was evident between the two groups. Hyponatremia of grade 3 or above developed in 30.7% of the generic CDDP group compared to 15.1% of the brand-name CDDP group (P=0.011). Multivariate analysis showed that the use of generic CDDP increased the incidence of hyponatremia (odds ratio =5.661, 95% confidence interval =1.403–22.839; P=0.015). Conclusion: Oncologists should be aware that use of a generic CDDP might be associated with more hyponatremia than would use of brand-name CDDP. Keywords: cisplatin, hyponatremia, brand-name, generic drug